1998
DOI: 10.1093/heapol/13.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Performance of village pharmacies and patient compliance after implementation of an essential drug programme in rural Burkina Faso

Abstract: After implementation of a nation-wide essential drug programme in Burkina Faso a prospective study was undertaken consisting of non-participant observation in the health centre and in the village pharmacy, and of household interviews with the patients. The study covered all general consultations in nine health centres in three districts over a two-week period as well as all client-vendor contacts in the corresponding village pharmacies; comprising 313 patients in consultations and 498 clients in eight village … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…31 McPake and Hongoro, 1995; Kravosec et al, 2000;Connor, 2000;Soeters and Griffiths, 2000. 32 Dong et al, 1999;Von Massow et al, 1998;Krause et al, 1998;Foster, 1991. 33 Bhat, 1996Bhat, 1999;DFID Health Systems Resource Center, 2000.…”
Section: Monitoring and Health Information Systemsmentioning
confidence: 99%
“…31 McPake and Hongoro, 1995; Kravosec et al, 2000;Connor, 2000;Soeters and Griffiths, 2000. 32 Dong et al, 1999;Von Massow et al, 1998;Krause et al, 1998;Foster, 1991. 33 Bhat, 1996Bhat, 1999;DFID Health Systems Resource Center, 2000.…”
Section: Monitoring and Health Information Systemsmentioning
confidence: 99%
“…Several health care reforms have been implemented in order to improve the health status of the population, but the impact on the wellbeing of the population was low [3,4]. Most depressing, the utilisation of health services has decreased during the last 15 years [5,6]. There is an ongoing debate about the reasons for this decline.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] In studies on the quality of drug prescription in rural health centres in Burkina Faso, only 33% of the patients received information on the duration of the treatment and 68% of the patients could recall the correct dosage of the drugs prescribed. 11 Lebitsa et al 12 found that only 11% and 21% of drugs dispensed at clinics and health posts, respectively, in Botswana had been adequately labelled, and sufficient knowledge about the drugs had been obtained by 56% and 57% of patients, respectively. This study concluded that, while the patterns of drug use in Botswana were not very different from those in other developing countries, a major problem exists with the dispensing process.…”
mentioning
confidence: 99%